Design and development of a planar MEMS microphone array - Pecioski, Damjan; Domazetovska Markovska, Simona; Gavriloski, Viktor; Anachkova, Maja; Shishkovski, Dejan; Angjusheva Ignjatovska, Anastasija (Institute of Noise Control Engineering (INCE), 2025)
In the last few years viewing an audio source has become a widely used tool in many fields such as speech recognition and enhancement and especially in noise localization in different environments. Acoustic cameras are widely used as a tool for noise source investigation, however an acoustic image is difficult to achieve in environments with a large amount of noise and reverberation. An effective approach to overcome this is the use of beamforming theory coupled with a microphone array in order to obtain a recording of the desired acoustic signal. The aim of this work is to design and develop a low cost microphone array which can be upgraded with a camera, i.e. acoustic camera, based on digital MEMS microphones and a raspberry pi. Different formations of the microphone array are developed, tested and compared. The details on hardware integration as well as the development environment are discussed in this paper.